Covid-19: Is wearing facemask necessary? - Lee, Pei May (The IIUM Covid19 Psychosocial Support Team, 2020)
After close to two months of Movement Control Order (MCO), the government decided to implement a more relaxed MCO, namely Conditional Movement Control Order (CMCO). People can now return to work, travel with a maximum of 4 people in a car beyond 10km, make non-essential trips such as dining in a restaurant, and perform many other activities that were prohibited during MCO. Though more freedom is granted under CMCO, people should be aware that the virus is still lingering around and we are still exposed to the risk of contracting the virus. As such, the easing of MCO does not equal to the return to normalcy. Instead, the whole society should raise its alert level and contribute to stopping the contagion of Covid-19. So, a pertinent question to be asked here is: What can we do to reduce the risk of infecting ourselves and others?